Pelatihan Pembuatan Teknik Joint Pada Produk Kapstok Kunci Dinding Untuk Siswa dan Siswi SMK - Mesah Nur Sejati; Aji Wicaksono; Dena Anggita (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
Background: Looking at developments in vocational schools, vocational schools in profile are education at the secondary level which has the aim of developing the skills possessed by female students. Basically, in this vocational school, skills are still obtained as a result of the direct learning process every day at the school. Then graduating students can immediately enter industry. The aim of this research is training in making joint techniques for wall lock kapstok products for vocational school students and female students. Training method for making joint techniques on wall lock kapstok products for vocational school students and students. First of all, through the preparation of reference images, the drawing process, the design process and the capstock making process (hemming process, forming process, engraving, finishing materials. There were 15 vocational school students participating. Results: Vocational school students understood the training in making joint techniques in Wall lock kapstok products Conclusion: So the training activity for making joint techniques on wall lock kapstok products for vocational school students and students is an activity that can raise existing problems, especially for vocational school students who previously knew about design science but Finally, we can produce functional Kapstok products.